PENGARUH FOREIGN DIRECT INVESMENT, TENAGA KERJA DAN KETERBUKAAN PERDAGANGAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Jimmy Nova; Nazaruddin Malik; Muhammad Sri Wahyudi (Jurnal Ilmu Ekonomi JIE, 2019)
Economic development is marked by an increase in economic growth as well as being able to promote economic growth. Indonesia is a developing country that has a fairly good economic growth and has increased from year to year, even though it had experienced an economic crisis that made Indonesia's economic growth unstable. This study aims to determine the effect of Foreign Direct Investment, labor and trade openness on economic growth in Indonesia. This study uses a quantitative approach. The data used is in the form of Indonesian secondary data from 1986-2017. The data analysis technique in this study uses time series using multiple regression models. The results show that: Partially, Foreign Direct Investment and labor have a positive and significant effect on economic growth in Indonesia, while trade openness has a negative and significant effect on economic growth in Indonesia. Simultaneously, it shows that the variables of Foreign Direct Investment, labor and trade openness have a significant effect on economic growth in Indonesia.